Modern physical metallurgy and materials engineering science, process, applications. - Smallman, R. E.; Bishop, R. J. (Ray J.) (Oxford ; Boston : Butterworth Heinemann, 1999)
For many years, various editions of Smallman's Modern Physical Metallurgy have served throughout the world as a standard undergraduate textbook on metals and alloys. In 1995, it was rewritten and enlarged to encompass the related subject of materials science and engineering and appeared under the title Metals & Materials: Science, Processes, Applications offering a comprehensive amount of a much wider range of engineering materials. Coverage ranged from pure elements to superalloys, from glasses to engineering ceramics, and from everyday plastics to in situ composites, Amongst other favourable reviews, Professor Bhadeshia of Cambridge University commented: "Given the amount of work that has obviously gone into this book and its extensive comments, it is very attractively priced. It is an excellent book to be recommend strongly for purchase by undergraduates in materials-related subjects, who should benefit greatly by owning a text containing so much knowledge." The book now includes new chapters on materials for sports equipment (golf, tennis, bicycles, skiing, etc.) and biomaterials (replacement joints, heart valves, tissue repair, etc.) - two of the most exciting and rewarding areas in current materials research and development. As in its predecessor, numerous examples are given of the ways in which knowledge of the relation between fine structure and properties has made it possible to optimise the service behaviour of traditional engineering materials and to develop completely new and exciting classes of materials. Special consideration is given to the crucial processing stage that enables materials to be produced as marketable commodities. Whilst attempting to produce a useful and relatively concise survey of key materials and their interrelationships, the authors have tried to make the subject accessible to a wide range of readers, to provide insights into specialised methods of examination and to convey the excitement of the atmosphere in which new materials are conceived and developed.
Structure and bonding of atoms; Atomic arrangements in materials; Structural phases; their formation and transitions; Defects in solids; Characterisation of materials; Physical properties of materials; Mechanical behaviour of materials; Strengthening and toughening; Modern alloy developments; Ceramics and glasses; Plastics and composites; Corrosion and surface engineering; Biomaterials; Materials for sports; Guide to SI Units; Conversion factors; constants and physical data.
Includes bibliographical references and index.
Keywords: Physical metallurgy; Electronic books